S-MANAGE Protocol for Provisioning IoT Applications on Demand - Nguyen, Chau; Hoang, Doan (Journal of Telecommunications and the Digital Economy, 2019)
Internet of Things (IoT)-based services have started making an impact in various domains, such as agriculture, smart farming, smart cities, personal health, and critical infrastructures. Sensor/IoT devices have become one of the indispensable elements in these IoT systems and services. However, their development is restricted by the rigidity of the current network infrastructure, which accommodates heterogeneous physical devices. Software-Defined Networking-Network Functions Virtualization (SDN-NFV) has emerged as a service-enabling solution, supporting network and network function programmability. Provisioning IoT applications on demand is a natural application of programmability. However, these technologies cannot be directly deployed in the sensing/monitoring domain due to the differences in the functionality of SDN network devices and sensor/IoT devices, as well as the limitation of resources in IoT devices. This paper proposes an S-MANAGE protocol that preserves the SDN-NFV paradigm but provides a practical solution in controlling and managing IoT resources for provisioning IoT applications on demand. S-MANAGE is proposed as a new southbound protocol between the software-defined IoT controller and its IoT elements. The paper presents the design of S-MANAGE and demonstrates its use in provisioning IoT services dynamically.